Student Perceptions of Criticism Ethics on Instagram: A Case Study of @Medantalk - Firman, Firman; Juliana Hasibuan, Effiati; Auza, Ara (Social Sciences and Humanities Reviews, 2025)
Background: The development of social media as a digital public space has changed the way individuals express opinions, including in the form of criticism. However, not all criticisms submitted meet the rules of communication ethics, thus giving rise to the phenomenon of offensive and unconstructive comments. Aims: This study aims to find out how Communication Science students of the University of Medan Area perceive the ethics of criticism on Instagram social media, especially on @Medantalk accounts which are often a public discussion space. Methods: This study uses a descriptive qualitative approach with interview and observation methods. Informants were selected by purposive sampling from active students who use Instagram. The data were analyzed using Miles and Huberman's interactive analysis techniques. Result: The results of the study show that most students have a negative perception of the practice of criticism on social media today. They assessed that many comments were not delivered politely, were not objective, and often contained hate speech. Conclusion: This perception shows the need to increase ethics-based digital literacy among students. In addition, learning digital communication ethics needs to be strengthened so that social media can become a healthy and constructive space for criticism.